Analisis Isi Naskah Berita Online Siswa Jurusan Produksi Siaran Pertelevisian SMK Negeri 5 Palembang - Junia Astuti; Nuraida Nuraida; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT In this research thesis entitled "Content Analysis of Online News Scripts of Students of Television Broadcast Production Department of SMK Negeri 5 Palembang". Mass media is a medium that is able to provide a wide and fast spread of information flow. Vocational secondary education is a school that prioritizes the development of students' abilities to be able to have abilities in certain types of work such as a journalist, newsanchor, director, and cameraman, graduates of this department are expected to have the ability to create quality mass media. The formulation of the problem of this research is how the ability to write online news scripts of students majoring in television broadcast production of SMK Negeri 5 Palembang and how efforts are made by schools to improve students' ability to write online news scripts, while the purpose of this research is to find out the ability of class X students of Television Broadcast Production of SMK Negeri 5 Palembang in writing online news scripts and to find out the efforts made by schools in improving students' ability to write online news scripts.The research method used is qualitative descriptive research. Data collection techniques using observation, interviews and documentation, the data sources of this research are class X students majoring in PSPT, mass communication teachers and department heads. The data analysis technique uses content analysis using Holsti's theory. The results of this study are that students have not been able to make online news scripts in full accordance with the structure of news writing and students use inverted pramida in making online news scripts, news elements, journalistic language and seen from the results of their practice of making online news scripts, Then for the development efforts made by the school, namely first preparing educators who are in accordance with the needs of the department, secondly providing laboratory rooms and school cinemas, thirdly facilitated to participate in various competitions, and fourthly forming extracurricular journalism and participating in competitions and managing smk5 TV, fifthly the availability of various types of literacy and digital attendance.